PENGGUNAAN APLIKASI E-VILLAGE BUDGETING DALAM MENGURANGI TINDAK PIDANA KORUPSI DI KABUPATEN BANYUWANGI - Khusnul Hatimah; Dewi Sekar Kencono (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2022)
This study aims to determine how the form of using the E-Village Budgeting application in reducing the occurrence of corruption cases in Banyuwangi Regency. This is because the development of corruption in Indonesia, especially in Banyuwangi Regency is still relatively high, while its eradication is still very slow. Therefore, there is a need for a special innovation such as E-Village Budgeting that can be used in conducting financial management in a transparent and accountable manner in order to reduce cases of criminal acts of corruption. This study uses qualitative research methods with data collection techniques namely literature study. The results obtained in this study indicate that the use of the E-Village Budgeting application in village financial management in Banyuwangi Regency has been running well. Transparency and accountability in village financial management through the E-Village Budgeting application is one of the right actions in reducing corruption cases in Banyuwangi Regency. With the rapid development of information technology not only has a negative impact, but also has a positive impact in this case the creation of an innovation that has a function, one of which is to reduce the occurrence of cases of corruption.